Case report: sub-clinical extramedullary B-ALL in the setting of relapse following targeted therapy - Johns, Claire; Erickson, Courtney; Jacobs, Ashley; Moon, Jennifer; Baggott, Christina; Dagher, Regina; Nadel, Helen; Balagtas, Jay; Aftandilian, Catherine; Ramakrishna, Sneha; Lacayo, Norman; Davis, Kara L.; et al. (Frontiers in Immunology, 2024)
Standard testing for disease evaluation in B-cell acute lymphoblastic leukemia (B-ALL) includes examination of the bone marrow and cerebrospinal fluid. Radiographic or functional imaging are indicated when clinical signs of non-CNS extramedullary disease are present but are not standard in the relapsed/refractory setting. We describe two cases of patients with relapsed/refractory B-ALL with prior exposure to blinatumomab and/or inotuzumab ozogamicin presenting for CAR-T cell treatment. Both patients were thought to only have minimal residual disease (MRD) at the pre-CAR disease assessment, with MRD of 6,648 (0.66%) and 100 (0.01%) cells per million cells, respectively, as measured by next-generation sequencing (NGS) in their bone marrows. Both patients for distinct reasons unrelated to non-CNS extra-medullary (EM) symptoms had PET-MRIs prior to lymphodepletion and CAR T cell infusion. In both cases patients were found to have significant bulky subclinical EM disease that required changes in clinical management. In the newly-emergent era of antigen-targeted immunotherapy, it is foundational that incidence and relapse patterns following targeted therapy are well-understood. Herein we contribute to a growing body of literature addressing this fundamental clinical gap and highlight a future role for formal prospective imaging studies to better establish response, toxicity and relapse patterns following CAR-T cell therapy in EM B-ALL.